Therapeutic Drug Monitoring of Antithyroid Drugs in Pregnancy: The Knowledge Gaps - Koren, Gideon (2006)
Despite being a common condition in pregnancy, and despite propylthiouracil (PTU) being perceived as safer than methimazole, there are virtually no epidemiological controlled studies on malformation rate an neurobehavioral outcomes with the former. This knowledge gap must be filled to ensure fetal safety.